Empowering Elementary Science Learning Through Articulate Storyline 3-Based Interactive Digital Media - Gani, Resyi Abdul; Windiyani, Tustiyana (Proceeding International Conference on Education, 2025)
Development of Interactive Learning Media Using Articulate Storyline Three in the learning of social studies landscape materials aims to strengthen the learning of social studies the development and feasibility of a product development through interactive learning media. The research methodology used was the ADDIE (Analyze, Design, Development, Implementation, Evaluation) approach with the research subjects of grade IV-B SDN Julang Bogor City, the instruments used were validation sheets of media experts, linguists and subject matter experts with a total of three experts, student response instruments and teacher responses, and pre-test and post-test instruments. The validation results produced an average of 94% with the criterion of "Very Feasible", then the results of the pre-test and post-test assessments produced an N-Gain score of 0.70 with the criterion of "High" and the response of students who obtained 98.7% and the teacher 88% with the criterion of "Very Good". Based on the results obtained, the development of interactive learning media using Articulate Storyline Three meets the valid and feasibility criteria for the development of IPAS learning landscape materials: characteristics and their relationship with the community profession.